PEMBERIAN IDENTITAS PENDUDUK PEKERJA SEKTOR INFORMAL DI JAKARTA MENURUT UNDANG – UNDANG NOMOR 23 TAHUN 2006 - Kholiah Qurtubi, Untung Sri Hardjanto, Retno Saraswati (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Administration of population in Indonesia is a very important rule in development. Act No.23 of 2006 has set the administration that in it enforces the use of the Population Administration Information System (SIAK) which aims to provide information to support the administration that is in line with advances in information and communications technology to meet the demands of the public for the service professional population. The number of migrants working in the informal sector who do not know how to get an ID and they did not take care of migrate letter which resulted in increased population growth in Jakarta. Thus, the SIAK can assist the Government in the record will be more efficient and effective. The method used is the normative juridical approach used to determine the legal norms contained in the legislation. Specifications research in legal writing is descriptive analysis, the study describes the legislation in force associated with the theories of law and positive law concerning the implementation of the above- mentioned problems. The result of the study is the presence SIAK governing the manufacture of residence identification card, family card, and other population letter will be more effective than the manufacture of identity cards that do not use SIAK. This is because the manufacturing process is cheaper and faster.